Excitation of vibrational quanta in furfural by intermediate-energy electrons - Jones, D.B.; Neves, R.F.C.; Lopes, M.C.A.; da Costa, R.F.; Varella, M.T.N.; Bettega, M.H.F.; Lima, M.A.P.; Garcia, G.; Blanco, F.; Brunger, M.J. (American Institute of Physics, 2015)
We report cross sections for electron-impact excitation of vibrational quanta in furfural, at intermediate incident electron energies (20, 30, and 40 eV). The present differential cross sections are measured over the scattered electron angular range 10 degrees-90 degrees, with corresponding integral cross sections subsequently being determined. Furfural is a viable plant-derived alternative to petrochemicals, being produced via low-temperature plasma treatment of biomass. Current yields, however, need to be significantly improved, possibly through modelling, with the present cross sections being an important component of such simulations. To the best of our knowledge, there are no other cross sections for vibrational excitation of furfural available in the literature, so the present data are valuable for this important molecule. (C) 2015 AIP Publishing LLC.